Wojna w eterze : wspomnienia - Nowak, Jan, 1913-; Nowak, Jan 1913- (Londyn : Odnowa, 1986)
Biography of the Polish journalist.
t. 1. 1948-1956 -- t. 2. Polska z oddali : 1956-1976.
Includes bibliographical references and index.
Keywords: Nowak, Jan, -- 1913-; Radio Free Europe -- Biography; Journalists -- Poland -- Biography; Poland -- Politics and government -- 1945-1980.